Pencegahan Resiko Jatuh pada Pasien dengan Diagnosis Keperawatan Dypsneu: Studi Kasus - Tambunan, Cristina Esria Valentin; Afandi, Alfid Tri; Nur, Kholid Rosyidi Muhammad; Wahyuni, Sri (Jurnal Keperawatan Sehat Mandiri, 2024)
Background: Patient safety is a system used to improve patient care in a relatively safer manner, including risk assessment, patient risk identification and management, case reporting and analysis, the ability to learn from cases, as well as follow-up and implementation of solutions to reduce risk and prevent injury resulting from errors caused by implementation or negligence of action procedures that must be taken. Method: The method used in writing this nurse's scientific work is descriptive qualitative and case study. Results: With the results observed for 3 days, Mrs M is a patient with a high risk of falling. Where a score of more than 45 is a high fall risk category and a score of less than 45 is a mild to moderate fall risk category. Conclusion: The role of professional nurses is as care giver, client advocate, counselor, educator, collaborator, coordinator, change agent, consultant. Application in preventing the risk of falls is by carrying out an initial assessment and re-assessment and intervention - education.